Physical and Aerodynamic Properties of Lavender in relation to Harvest Mechanisation - Christos I. Dimitriadis; James L. Brighton; Mike J. O’Dogherty; Maria I. Kokkora; Anastasios I. Darras (International Journal of Agronomy)
A laboratory study evaluated the physical and aerodynamic properties of lavender cultivars in relation to the design of an improved lavender harvester that allows removal of flowers from the stem using the stripping method. The identification of the flower head adhesion, stem breakage, and aerodynamic drag forces were conducted using an Instron 1122 instrument. Measurements on five lavender cultivars at harvest moisture content showed that the overall mean flower detachment force from the stem was 11.2 N, the mean stem tensile strength was 36.7 N, and the calculated mean ultimate tensile stress of the stem was 17.3 MPa. The aerodynamic measurements showed that the drag force is related with the flower surface area. Increasing the surface area of the flower head by 93% of the “Hidcote” cultivar produced an increase in drag force of between 24.8% and 50.6% for airflow rates of 24 and 65 m s−1, respectively. The terminal velocities of the flower heads of the cultivar ranged between 4.5 and 5.9 m s−1, which results in a mean drag coefficient of 0.44. The values of drag coefficients were compatible with well-established values for the appropriate Reynolds numbers.